Fungsi Kognitif Anak Dengan Epilepsi Umum - I Gusti Ngurah Made Suwarba; Ni Wayan Kurnia Wati (Buletin Penelitian Sistem Kesehatan, 2022)
Children with epilepsy may experience cognitive impairment due to the effects of structural lesions or seizure activity. This study aims to determine the cognitive function of children with general epilepsy. This study was a cross-sectional design that included children aged 6 to 68 months with general epilepsy in the polyclinic and pediatric ward of Sanglah Hospital Denpasar from September 2013 to January 2015. All children who participated in this study were subjected to a Mullen scale examination. Statistical analysis was performed using Chi-square test and multivariate analysis with logistic regression. In 93 children with general epilepsy, there was a significant correlation between the level of cognitive function and seizure frequency >10 times with an odds ratio 6.067 (95% CI 2.002-18.388, p value 0.001) and seizure duration ≥15 minutes with an odds ratio 6.006 (95% CI 1,817-20,246, p value 0.003). In this study, it can be concluded that seizure frequency >10 times and seizure duration ≥15 minutes in children with general epilepsy have a positive relationship of 6 times with the abnormal cognitive function. Further studies are needed to determine cognitive development of children with general epilepsy. Abstrak Anak dengan epilepsi dapat mengalami gangguan kognitif berkaitan dengan efek dari lesi struktural maupun aktivitas kejang. Penelitian ini ditujukan untuk mengetahui fungsi kognitif anak dengan epilepsi umum. Penelitian ini merupakan penelitian dengan desain potong lintang yang mengikutsertakan anak usia 6 sampai 68 bulan dengan epilepsi umum di poliklinik dan ruang perawatan anak RSUP Sanglah Denpasar pada bulan September 2013 hingga Januari 2015. Semua anak yang ikut serta dalam penelitian dilakukan pemeriksaan skala Mullen. Analisis statistik dilakukan dengan uji kai kuadrat dan analisis multivariat dengan regresi logistik. Pada 93 anak dengan epilepsi umum, didapatkan hubungan yang signifikan antara fungsi kognitif dengan frekuensi kejang >10 kali dengan rasio odds 6,067 (nilai p=0,001, 95% CI 2,002-18,388) dan lama kejang ≥15 menit dengan rasio odds 6,006 (nilai p=0,003, 95% CI 1,817-20,246). Pada penelitian ini dapat disimpulkan bahwa frekuensi kejang >10 kali dan lama kejang ≥15 menit pada anak dengan epilepsi umum memiliki hubungan yang positif sebesar 6 kali terhadap fungsi kognitif abnormal. Penelitian lanjutan perlu dilakukan untuk mengetahui perkembangan fungsi kognitif anak dengan epilepsi umum.